The Salience of Work from Home Policy in Street-Level Bureaucracy for Managing Immigration Services - Gunawan Ari Nursanto; Besse Hartati; Catur Susaningsih; Rasona Sunara Akbar; Cakra Trinata; Mila Rosmaya (International Journal of Qualitative Research, 2026)
This study examines the implementation of work-from-home (WFH) arrangements in Indonesian immigration public service delivery through the lens of street-level bureaucracy. The study is situated within the 2026 policy context, in which WFH was introduced as a crisis-responsive governance measure to reduce mobility, support energy efficiency, and maintain public-sector productivity amid global energy uncertainty. Using a qualitative descriptive-analytical approach, this study combines document analysis of national and sectoral WFH regulations with non-participant observation of frontline immigration service practices in five Immigration Offices in Jabodetabek. The findings show that WFH in immigration services cannot be applied uniformly because immigration work combines administrative service, legal authority, identity verification, public interaction, and state security functions. Remote work is suitable for administrative and document-based tasks, while biometric capture, passport interviews, detention management, immigration checkpoints, and enforcement functions require physical presence. The study concludes that WFH should be governed as a controlled hybrid mechanism supported by task classification, digital supervision, data protection, output-based accountability, and service-continuity safeguards.